Nanoarchitectonic Design of Complex Materials Using Polymer Brushes as Structural and Functional Units - Cortez, María Lorena (2017)
Polymer brushes have become versatile building blocks for the construction of more complex hybrid materials. In this chapter, we review recent developments involving the use of polymer brushes combined with a variety of nanomaterials. Nanoarchitectonics refers to the rational organization of nanostructures into functional materials with precise control of the position at the nanoscale. In this scenario, polymer brushes are integrated via two main approaches: either produced by controlled surface-initiated polymerization from nanometric templates or acting as nanoreactors/stabilizers/capping agents for further synthesis of confined inorganic nanostructures. In any case, the utilization of both templated or template polymer brushes results in an intimate integration of the nanobuilding blocks that yields dimensionally stable nanoarchitectures. Far from being exhaustive, the following selection of systems pretend to be examples that illustrate not only the multiplicity of techniques and approaches reported in the past years but also the potentialities and perspectives of use of polymer brushes in this multidisciplinary field of nanoarchitectonics.